Characteristics of board composition and their influences on financial performance: can family firms be differently affected? - Mesnik, Samy Sznajder (2023)
Family firms may adopt different corporate governance practices and face particular agency problems between executives and board members. This study embraces the most extensive and unstructured data in the region to deliver an updated empirical-quantitative papers that demonstrates the impact of the presence of outside directors on the board of directors could be different across family vs. non-family firms regarding the financial performance. Also, I provide evidence that board independence has a statistically significant positive impact on firm performance for a specific cohort of family firms and that the outcomes are antagonistic for cases of CEO duality. This suggests that the presence of outside directors in the board is relevant to explain firm performance of family firms, because they better deal with mechanisms that reduce the type II agency conflicts. In addition to that, I have investigated the relationship of board membership changes and financial performance, including different configurations of the functions and whether this effect is more pronounced for family firms over non-family firms. Finally, I have investigated whether the tenure of the board members is significant in this equation. After a series of robustness tests, the results indicate that board membership changes are significant for family firms towards a short-term financial performance indicator, with positive effect above a certain interval. The long-term financial performance indicator measured in this study has not demonstrated to be significant, though the signaling to the market of board membership changes should not be relevant. Based on the agency theory and the stewardship perspective, this study delves into the analysis of family firms and considers different clusters of companies dissociated by corporate governance characteristics related to the structure of the board of directors and provide insightful evidence for academics, policymakers, investors and practitioners.